MATHEMATICAL MODEL OF CHANGING THE DATA RATE DEPENDING ON THE LENGTH OF THE SEGMENT OF THE SPECIALIZED DIGITAL NETWORK COMLI BASED ON CURRENT LOOP - Бабчук, Сергей (SWorldJournal, 2021)
In a specialized digital network COMLI based on Current loop, the data rate depends on the length of the network segment. A mathematical model of changing the data rate depending on the length of the segment of the specialized digital network COMLI based